The Effect of Financial and Digital Literacy Toward QRIS Usage - Muhammad Arief Waliyuddin; Raden Aswin Rahadi (Riviera Publishing, 2023)
Introduction: Internet penetration in Indonesia has reached 77%, with 21.6% of Indonesian users using mobile payments, and this shows that the use of QRIS has growth potential. Many variables are affected by QRIS, so this research aims to determine and analyze the influence of Financial and Digital literacy on QRIS. Method: This study used quantitative methodology and involved 424 Indonesian respondents. This study used the Purposive Sampling Technique for sampling. The study was based on primary data collected through questionnaires. The data analysis approach uses binary logistic regression. Result: Based on the results of the study, the financial literacy calculation (X1) was 5,423 with a P-value of 0.020 and the digital literacy calculation value (X2) of 4.269, with a P-value of 0.039 while the table for significance was 0.05 and df (nk) 424 – 3 = 421, namely 1,966. Based on this, it was decided to reject Ho, which means that financial literacy and digital literacy partially affect the use of QRIS. Conclusion: Based on the findings of this study, financial and digital literacy variables partially & simultaneously did not have a significant effect but had favourable odds on the use of QRIS payments.